Rare cases encountered in otolaryngology and head neck surgery - Maqbool, Tabish; Mehta, Kulvinder Singh; Showkat, Showkat Ahmed; Ahmed, Rauf (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
In our day to day otolaryngological practice we encounter many cases, some of which are very rare and worth reporting. We report very rare three cases seen during our practice: presence of tooth in anterior ethamoids causing chronic sinusitis, and NK/T Cell lymphoma (nasal variant) and An accessory submandibular gland. There have been few case reports which mentions about the presence of tooth in maxillary sinus leading to sinusitis but none mentions of presence of the tooth in anterior ethamoids leading to sinusitis. Extranodal NK/T cell lymphoma, nasal variant is a rare and aggressive type of non-Hodgkin’s lymphoma that develops outside the lymphatic system especially in the nose. Accessory submandibular gland is extremely rare. This is the fifth case reported so far worldwide.